2003
DOI: 10.1002/glia.10237
|View full text |Cite
|
Sign up to set email alerts
|

Pepstatin A induces extracellular acidification distinct from aspartic protease inhibition in microglial cell lines

Abstract: The extrusion of protons is considered a very general parameter of the activation of many kinds of membrane or intracellular molecules, such as receptors, ion channels, and enzymes. We found that pepstatin A caused a reproducible, concentration-related increase in the extracellular acidification rate in two microglial cell lines, Ra2 and 6-3. Washing abolished pepstatin A-induced acidification immediately. However, pepstatin A did not cause the extracellular acidification in other cell types, such as CHO, C6 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…These results were somewhat unexpected,since it is well known that pepstatin A inhibits the proteolysis of aspartic acid proteases that in turn inhibit endosomal acidification (Zaidi et al, 2007), which should affect significantly VACV entry via the endocytic route. However, Okada and co-workers reported that pepstatin A also displays an alternative role inducing extracellular acidification, which is unrelated to its inhibition of aspartic proteases (Okada et al, 2003). We conlcude that the external acidification produced via pepstatin does not significantly affect MYXV and VACV entry into these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results were somewhat unexpected,since it is well known that pepstatin A inhibits the proteolysis of aspartic acid proteases that in turn inhibit endosomal acidification (Zaidi et al, 2007), which should affect significantly VACV entry via the endocytic route. However, Okada and co-workers reported that pepstatin A also displays an alternative role inducing extracellular acidification, which is unrelated to its inhibition of aspartic proteases (Okada et al, 2003). We conlcude that the external acidification produced via pepstatin does not significantly affect MYXV and VACV entry into these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Microglia are known to consist of various subpopulations 23–26 . It is of note that the SMK cell line was cloned from a single cell by the limiting dilution method and does not necessarily represent the subpopulation of microglia that can be isolated by the current method.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that production of IL-12 [151] and histamine [152] are different in the subtypes of microglia. Furthermore, the subtypes of microglia show distinct acidification profiles by treatment with pepstatin A [153] and selective clearance of oligomeric beta-amyloid peptide [154]. The distinct phenotypes in activated forms of microglia might result from this heterogeneity.…”
Section: Microglia Diversitymentioning
confidence: 99%